2019
DOI: 10.1038/s41598-019-39537-z
|View full text |Cite
|
Sign up to set email alerts
|

DGAT1 Inhibitor Suppresses Prostate Tumor Growth and Migration by Regulating Intracellular Lipids and Non-Centrosomal MTOC Protein GM130

Abstract: Acyl-CoA:diacylglycerol acyltransferase I (DGAT1) is a key enzyme in lipogenesis which is increased in metabolically active cells to meet nutrient requirements. DGAT1 has been recognized as an anti-obesity target; however, its role in the tumor microenvironment remains unclear. We postulated that, in prostate cancer (PCa) cells, augmented lipogenesis and growth are due to increased DGAT1 expression leading to microtubule-organizing center (MTOC) amplification. Thus, therapeutic targeting of DGAT1 potentially h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Immunofluorescence (IF) staining was performed as described previously 46,47 . Immunohistochemistry and semiquantitative scoring techniques were performed as described previously 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence (IF) staining was performed as described previously 46,47 . Immunohistochemistry and semiquantitative scoring techniques were performed as described previously 48 .…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that pharmacological inhibition of DGAT1 in breast and prostate cancer cells blunted TG synthesis and influenced cell viability [ 3 , 4 ]. Likewise, knockdown of DGAT1 reduced lipid droplet number and cell proliferation and invasion of prostate cancer cells [ 135 , 247 ] and glioblastoma [ 246 ]. However, the protein levels of DGAT2 are reduced in HCC, and overexpression of DGAT2 inhibits cell proliferation and colony formation in vitro and tumor formation in vivo [ 248 ].…”
Section: Tumor Fatty Acid Metabolism Pathways and Their Role In Cancementioning
confidence: 99%
“…8-9). DGAT1 encodes a key enzyme in lipogenesis, which was found increased in prostate cancer cells and could facilitate cell proliferation and migration 34 . DGAT1 gene expression was increased in both SRCCs and STADs (TCGA cohort) than non-malignant pairs, suggesting its increased expression in stomach adenocarcinoma universally.…”
Section: Discussionmentioning
confidence: 99%